Penerapan Model Pembelajaran Connecting, Organizing, Reflecting, Extending (CORE) dalam Meningkatkan Hasil Belajar IPA Materi Hubungan Gaya dan Gerak pada Siswa Kelas IV di UPTD SD Negeri 46 Parepapare - Ila Israwaty; Kamaruddin Hasan; Putri Ayu Lestary (Universitas Negeri Makassar, 2022)
This study examines the application of learning models Connecting, Organizing, Reflecting, Extending (CORE) in improving learning outcomes science material relationship of style and motion in fourth grade students in UPTD SD Negeri 46 Parepare. The type of research used is Class Action Research (PTK) using a qualitative approach. The focus of this research is the focus of the process and the focus of the results. The subjects of this study were teachers and fourth grade students of UPTD SD Negeri 46 Parepare, as many as 32 students consisting of 13 men and 19 women. Data is obtained through test techniques, observations, and documentation. The results showed that in the first cycle the results of observation of teacher activity were 83% with good categories and observation of student activity was 72,91% with enough categories. In the second cycle, there was an increase in the results of observation of teacher activity to 89% with good categories and observation of student activity to 85,93% with good categories. The results were related to learning outcomes, in the first cycle only 53% were completed with an average of 73,75. In the second cycle increased to 87,5% of students who completed with an average of 86,25. The conclusion of this research is through the application of learning models Connecting, Organizing, Reflecting, Extending (CORE) on the material of the relationship of style and motion can improve the learning outcomes of fourth grade students UPTD SD Negeri 46 Parepare.